Gauging Long-Term Knowledge Retention of Forensic Science: A Follow-Up Study of College Students Who Participated in a Crime Scene Simulation - Byrne, David S (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2022)
This is a long-term follow-up to a prior study which found that simulations enhance knowledge retention of undergraduate students who had participated in a mock crime scene. Employing the qualitative method, three participants from the original research were interviewed 1- to 3-years later and asked a series of questions relating to their coursework on forensic science. Findings revealed that long-term knowledge of the major theories relating to the subject domain remained stable over time. It was only the responses to questions regarding specific terminology that presented a gradual decline which is consistent with the decay of semantic memory. Furthermore, each of the subjects were able to recall exactly when during the mock crime scene that they experienced or solved the interview question posited. The ability to trace back and pinpoint the task that prompted the learning and reinforcement of the concept is aligned with episodical memory. Overall, the results indicated that classroom simulations improve long-term knowledge retention of forensic science students.